The Influence of Pregnancy on Sweet Taste Perception and Plaque Acidogenicity - Sonbul, H.; Ashi, H.; Aljahdali, E.; Campus, G.; Lingström, P. (Maternal and child health journal, 2017)
Objectives Women undergo different physiological and oral changes during pregnancy and this may increase the risk of dental caries and other oral diseases. The aim of the present study was to investigate changes in biofilm acidogenicity and correlate them to sweet taste perception in pregnant and non-pregnant women. Methods Three groups of Saudi women participated in this cross-sectional study: (1) women in early pregnancy (n = 40/mean age 29.6 years/DMFT 10.7), (2) women in late pregnancy (n = 40/29.5 years/DMFT 10.8) and (3) non-pregnant women (n = 41/27.7 years/DMFT 12.3). Changes in plaque pH were determined by using colour-coded indicator strips before and after a 1-min rinse with a 10% sucrose solution. A taste perception test determining sweet preference and threshold levels was also performed. Results A significant difference regarding plaque pH was seen between the early, late and non-pregnant women when calculated as the area under the curve ( p < 0.05). Regarding the taste perception tests, taste preference and threshold were correlated ( p < 0.001, r = 0.6). Between the three groups, a statistically significant difference was seen in taste threshold and taste preference respectively ( p = 0.001 and p < 0.001). Conclusions The findings in this study suggest that pregnant women may undergo taste changes and experience lower plaque pH, which may result in an increased risk of dental caries.